Physical, textural and crystallization properties of ground nut oil-based diacylglycerols in W/O margarine system - Ke, Wanting; Lee, Yee-Ying; Cheng, Jianqiang; Tan, Chin-Ping; Lai, Oi-Ming; Li, Aijun; Wang, Yong; Zhang, Zhen (Elsevier, 2023)
Enzymatic glycerolysis produced ground nut oil-based diacylglycerols (GNO-DAG) with a purity of 43.28 ± 0.89 (GNO-DAG40). GNO-DAG80 (with a DAG purity of 87.33 ± 0.61) was obtained after purification using molecular distillation. Traditional palm oil was mixed with the “liquid” DAG as margarine base oils. Subsequent evaluations of palm oil-DAG-based fats (PO-GNO DAG) as a margarine replacement in a W/O model system showed that the material was an ideal functional base oil with improved aeration properties and plasticity during application. The binary system physical, textural and crystallization property were determined, and the compatibility of the binary mixed system was analyzed by constructing a phase diagrams. The PO-GNO DAG showed decent compatibility between the two phases and had better texture and rheological properties. In addition, PO-GNO DAG40 showed better apparent viscosity and aeration characteristics than PO-GNO DAG80, with potential application in the food specialty fats industry.